Meteorin-like levels are associated with active brown adipose tissue in early infancy - Garcia-Beltran, Cristina; Navarro-Gascon, Artur; López-Bermejo, Abel; Quesada-López, Tania; de Zegher, Francis; Ibáñez, Lourdes; Villarroya, Francesc (Frontiers in Endocrinology, 2023)
Introduction: Meteorin-like (METRNL) is a hormonal factor released by several tissues, including thermogenically active brown and beige adipose tissues. It exerts multiple beneficial effects on metabolic and cardiovascular systems in experimental models. However, the potential role of METRNL as brown adipokine in humans has not been investigated previously, particularly in relation to the metabolic adaptations taking place in early life, when brown adipose tissue (BAT) is particularly abundant. Methods and Materials: METRNL levels, as well as body composition (DXA) and circulating endocrine-metabolic variables, were assessed longitudinally in a cohort of infants at birth, and at ages 4 and 12 months. BAT activity was measured by infrared thermography at age 12 months. METRNL levels were also determined cross-sectionally in adults; METRNL gene expression (qRT-PCR) was assessed in BAT and liver samples from neonates, and in adipose tissue and liver samples form adults. Simpson-Golabi-Behmel Syndrome (SGBS) adipose cells were thermogenically activated using cAMP, and METRNL gene expression and METRNL protein released were analysed. Results: serum METRNL levels were high at birth and declined across the first year of life albeit remaining higher than in adulthood. At age 4 and 12 months, METRNL levels correlated positively with circulating C-X-C motif chemokine ligand 14 (CXCL14), a chemokine released by thermogenically active BAT, but not with parameters of adiposity or metabolic status. METRNL levels also correlated positively with infrared thermography-estimated posterior-cervical BAT activity in girls aged 12 months. Gene expression analysis indicated high levels of METRNL mRNA in neonatal BAT. Thermogenic stimulus of brown/beige adipocytes led to a significant increase of METRNL gene expression and METRN protein release to the cell culture medium. Conclusion: circulating METRNL levels are high in the first year of life and correlate with indices of BAT activity and with levels of an established brown adipokine such as CXCL14. These data, in addition with the high expression of METRNL in neonatal BAT and in thermogenically-stimulated brown/beige adipocytes, suggest that METRNL is actively secreted by BAT and may be a circulating biomarker of BAT activity in early life.